Viral CD229 (Ly9) homologs as new manipulators of host immunity. Issue 5 (21st February 2019) - Angulo, Ana; Cuenca, Marta; Martínez‐Vicente, Pablo; Engel, Pablo
Abstract: The signaling lymphocytic activation molecule family (SLAMF) of receptors plays crucial roles during innate and adaptive immune responses. The SLAMF member CD229 (Ly9, SLAMF3) is a homophilic receptor predominantly expressed on the surface of B and T cells. CD229 acts as a cosignaling molecule, regulating lymphocyte homoeostasis and activation. To promote viral replication and survival in their hosts, viruses have developed sophisticated mechanisms to combat and avoid immune surveillance. Many of these strategies rely on host defense genes captured during the process of virus–host coevolution. In particular, large DNA viruses devote a wide range of proteins to interfere with almost every host immune pathway. Given that CD229 is critically involved in regulating immune responses, it is not surprising that viruses have designed tactics to mimic or interfere with this receptor. The discovery, in recent years, that some viruses have hijacked CD229 genes from their hosts, incorporating them as an integral part of their genomes, or have evolved proteins to directly target CD229, indicates that this is the case. While it is still an emerging area of research, the present review discusses these viral molecules and their potential in immune modulation. A more detailed understanding of the mechanisms of action and the functional implications of these new viral CD229 mimics may not only provide seminal information on viral immune evasion mechanisms but also, unveil unrecognized aspects of CD229 immune functions. Abstract : Review of viral genes captured during evolution, encoding CD229 leukocyte surface homologs, target cells of the immune system to induce viral escape.